Combined effect of ambient temperature and solar radiation on maned sloths' behaviour and detectability - Lopes, Gabriel S.; Cassano, Camila Righetto; Mureb, Laila Santim; Miranda, Flavia Regina; Cruz-Neto, Ariovaldo P. [UNESP]; Giné, Gastón Andrés Fernandez (Wiley, 2023)
Changes in ambient temperature and solar radiation may affect sloths' metabolic rate and body temperature, with consequent changes in activities, postures and microhabitat selection. Although the separate effect of temperature and solar radiation on sloth's behaviour have been previously studied, the combined effect of these climatic factors on behavioural aspects of sloths has never been systematically evaluated in field conditions. Here we evaluated the influence of hourly ambient temperature variation on maned sloth (Bradypus torquatus) activities, postures and tree crown positions, under sunny and cloudy conditions; and tested if any of the animal posture and position increase their exposure to human detection. We performed 350 h of visual observation on eight maned sloths, equipped with radio-backpacks, in northern Bahia, Brazil, recording their activities, and their resting postures and positions on tree crowns. We also recorded the time taken to visualize the sloths on 58 days to analyse if sloths' detection is affected by posture and position. Higher ambient temperature, within a range of 21–33°C, increased the sloths' activity levels in cloudy conditions but reduced their activity in sunny conditions. Increasing ambient temperature also reduced the frequency of huddled posture and increased the frequency of extended posture and permanence in the inner tree crown. Lastly, the postures and positions did not influence sloths' detectability. Thus, the direction of the temperature–activity relationship depends on climatic conditions (sunny/cloudy), and individuals rely on resting postures and positions to thermoregulate. The warmer and drier future climate, expected to occur in the northern Atlantic Forest, may impose change in the diurnal activity levels and postural pattern for this threatened species, leading maned sloths to reduce its activity on sunny and warmer days and adopting an extended posture.
Keywords: activity; arboreal mammal; Bradypus torquatus; folivore; thermal response